2022
DOI: 10.3390/md20010054
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an Insoluble and Soluble Form of Melanin Produced by Streptomyces cavourensis SV 21, a Sea Cucumber Associated Bacterium

Abstract: Melanin is a widely distributed and striking dark-colored pigment produced by countless living organisms. Although a wide range of bioactivities have been recognized, there are still major constraints in using melanin for biotechnological applications such as its fragmentary known chemical structure and its insolubility in inorganic and organic solvents. In this study, a bacterial culture of Streptomyces cavourensis SV 21 produced two distinct forms of melanin: (1) a particulate, insoluble form as well as (2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 46 publications
(76 reference statements)
2
13
0
Order By: Relevance
“…Using AntiSMASH, in silico prediction of secondary metabolite biosynthetic gene clusters identified a total of 25 clusters with similarity to known clusters of ≥ 16%. Of those, 4 biosynthetic gene clusters including desferrioxamin, melanin, coelichelin, and isorenieratene were reported to be antioxidant and iron chelating agents (Table S6) (Hu et al 2018;Chen et al 2019;Williams et al 2019;Wibowo et al 2022). This was in agreement with the DPPH, reducing power, superoxide radical scavenging activities observed, indicating the ability of strain VCCM 22513 to produce 4 antioxidant compounds.…”
Section: Primary Responses Of S Parvulus Vccm 22513 To Oxidative Stresssupporting
confidence: 70%
“…Using AntiSMASH, in silico prediction of secondary metabolite biosynthetic gene clusters identified a total of 25 clusters with similarity to known clusters of ≥ 16%. Of those, 4 biosynthetic gene clusters including desferrioxamin, melanin, coelichelin, and isorenieratene were reported to be antioxidant and iron chelating agents (Table S6) (Hu et al 2018;Chen et al 2019;Williams et al 2019;Wibowo et al 2022). This was in agreement with the DPPH, reducing power, superoxide radical scavenging activities observed, indicating the ability of strain VCCM 22513 to produce 4 antioxidant compounds.…”
Section: Primary Responses Of S Parvulus Vccm 22513 To Oxidative Stresssupporting
confidence: 70%
“…Production of melanin from microorganisms has been an environmentally friendly approach and economical alternative to the chemical synthesis of melanin [ 6 ]. Melanins are available in different forms, such as eumelanin, pheomelanin, and allomelanins [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The crude extract of S. tubbatahanensis DSD3025 T had an oily consistency with dark brown coloration due to the high pigmented melanin content ( 55 , 56 ). Initial screening using an absorbance-based assay revealed that the nature of S. tubbatahanensis DSD3025 T extract caused false-positive results and low reproducibility.…”
Section: Resultsmentioning
confidence: 99%